2023
DOI: 10.3389/fimmu.2023.1135861
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the fecal and vaginal microbiomes in patients with systemic lupus erythematosus and their associations with immunological profiles

Abstract: BackgroundExploring the human microbiome in multiple body niches is beneficial for clinicians to determine which microbial dysbiosis should be targeted first. We aimed to study whether both the fecal and vaginal microbiomes are disrupted in SLE patients and whether they are correlated, as well as their associations with immunological features.MethodsA group of 30 SLE patients and 30 BMI-age-matched healthy controls were recruited. Fecal and vaginal samples were collected, the 16S rRNA gene was sequenced to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, we found that blood enrichment of Shigella was increased in Black controls versus White controls and decreased in Black patients versus White patients. Vaginal Escherichia and Shigella enrichment was negatively associated with serum C4 in patients with SLE 41 . Thus, Shigella may have negative association with SLE in Black patients.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, we found that blood enrichment of Shigella was increased in Black controls versus White controls and decreased in Black patients versus White patients. Vaginal Escherichia and Shigella enrichment was negatively associated with serum C4 in patients with SLE 41 . Thus, Shigella may have negative association with SLE in Black patients.…”
Section: Discussionmentioning
confidence: 90%
“…Vaginal Escherichia and Shigella enrichment was negatively associated with serum C4 in patients with SLE. 41 Thus, Shigella may have negative association with SLE in Black patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, a pilot study reported that human microbiota imbalance in SLE was associated with immunological characteristics of the patients, such as serum C4 levels, suggesting that normalization of the microbiota may restore dysregulated immunity in SLE patients [13] . Indicators of immune system health, such as impaired Tfh/Tfr, Th17/Treg ratios, and levels of inflammatory cytokines in mice and SLE patients, were also found to be associated with changes in gut microbiota composition [12] . All these data allow us to consider intestinal dysbiosis as an important element in the development of SLE, and efforts aimed at its normalization are quite suitable for the role of a new means of treating this disease.…”
Section: Introductionmentioning
confidence: 93%
“…The Ruminococcaceae family has also been found to produce SCFAs, and a decrease in these bacteria could lead to a reduction in SCFA production [92] . Another metabolite of gut bacteria, tryptophan, is also associated with the SLE severity, is metabolized differently in SLE patients, and may control the number of autoreactive helper T cells [12] . Dietary tryptophan was found to regulate the autoimmune system; a low dietary tryptophan prevented autoimmune disease in a mouse model of SLE, while a high dietary tryptophan exacerbated the disease [108] .…”
Section: Potential Mechanisms Linking Gut Microbiota To Sle Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation